Beyond Instruction: The Role of Emotional Intelligence Competencies in Enhancing Classroom Effectiveness - Laput, Margie; Oropa, Jane (Journal of Interdisciplinary Perspectives, 2025)
Emotional intelligence (EI) is recognized as a key factor in achieving educational goals and enhancing teacher effectiveness. This study assessed the level of EI competencies through validated questionnaire among 152 elementary school teachers in the San Francisco District of Agusan del Sur Division, Philippines. The study employed a descriptive correlational research design. Data were analyzed using statistical tools such as frequency count, percentage, mean, standard deviation, and Pearson correlation. Findings indicated high levels of EI competencies, with significant correlations between empathy and the number of mental health trainings attended (r = 0.241, p = 0.003), and between social skills and length of service (r = 0.189, p = 0.020). Specifically, teachers with more training and longer service demonstrated higher levels of empathy and social skills, respectively. The study identified areas needing improvement, particularly in adaptability, staying updated with best practices, recognizing students' emotional needs, and conflict resolution. To address these gaps, an action plan was developed for a comprehensive training program. This includes preparatory activities, needs assessment, curriculum planning, resource preparation, collaborative sessions, and continuous monitoring. The results highlighted the critical need for targeted training and constant support. Additionally, leveraging the expertise of experienced educators and ensuring the availability of resources and professional development opportunities. These efforts are expected to enhance teachers' emotional intelligence (EI) competencies, thereby improving the quality of education. The study's findings have significant policy implications, emphasizing the need for educational policymakers to integrate EI training in teacher development programs, allocate resources for continuous professional development, and establish robust support systems to enhance the effectiveness of EI competencies in schools.